Bacteriophage as a potential therapeutic agent against Salmonella enterica serovar typhimurium in local broiler chicken - Wong, Chuan Loo (2011)
Global expansion of the livestock industry and demand for the production of livestock products have increased noticeably in many developing countries. In Malaysia, poultry industry represents by far the largest proportion in the livestock industry in terms of livestock output-value. The marked expansion of poultry’s products in order to meet the demand for poultry meat led to the rapid increase in the incidence of zoonotic diseases and emergence of multi-drug resistant microorganisms, primarily resulted from the application of growth-promoting drugs in the animal production line. Salmonellosis remains one of the most frequently reported zoonotic diseases with Salmonella enterica serovar Typhimurium being the pre-dominant implicated serotype that is resistant to a great variety of antibiotics. In recent years, Salmonella specific-bacteriophages have been reported as a plausible alternative to antibiotics. Thus, the present study was carried out with the aim to isolate bacteriophages against local S. Typhimurium. The bacteriophage isolates were analysed by electron microscopy and their genomes were isolated to study their size and type, and restriction enzyme profile patterns. The structural proteins of the phages were also studied by SDS-PAGE. Phage growth was characterised by the one-step kinetics growth curve, adsorption rate, multiplicity of infection (MOI) ratios and the effects of different pHs and temperatures on phage-host interaction. Subsequently, the efficacy of a selected phage to reduce the host bacteria load in vivo was evaluated. In the present study, three lytic bacteriophages namely Φst1, Φst5 and Φst10 were isolated from poultry faecal materials. The morphology of these phages indicated that they belong to the Siphoviridae family. Φst1 was found to demonstrate a broader host range in which it was able to infect S. enterica serovar Hadar (S. Hadar) apart from S. Typhimurium, the original host in which it was isolated from. All the three phages were DNA phages harbouring a genome about 125 kbp size. Although all the three phages revealed similar protein profile when analysed using SDS-PAGE, they can be differentiated with distinctive restriction digestion profiles of EcoRI and BamHI. All three phages have a latent period ranging from 40-50 min and generated a burst size of 22 (Φst1), 10 (Φst5) and 29 (Φst10) particles per infective center, respectively. MOI optimisation results revealed that MOI ratio of 0.1 generated the highest bacteria reduction rate (~ 6 log cfu/ml) and an increment of ~ 4 log pfu/ml in phage titer. Φst1 was found to produce the highest adsorption rate (86.1%) within the first 5 min of infection, and subsequently followed by Φst10 (82.1%) and Φst5 (60.4%). Among the three phage isolates, Φst5 demonstrated a broader spectrum of pH tolerance (pH 5-11), in which ≤ 0.1 log pfu/ml decrease in phage titer was detected. However, under different pH conditions, Φst1 was observed to demonstrate the highest adsorption rates (88.4-92.2%) at pH 7-11, whereby the highest bacteria reduction (6.6 log cfu/ml) was observed at pH 9. In general, all the three phage isolates were stable at the temperatures (25 ºC, 37 ºC, 42 ºC and 60 ºC) tested with less than 0.5 log pfu/ml decrease in phage titer after 3 h of incubation. The three phages demonstrated the highest (5.9-6.4 log cfu/ml) and insignificant different reduction rate of host cells at 37 °C and 42 °C. Based on the overall characteristics of the phage isolates, Φst1 was selected for subsequent in vivo study. With the high titer application of Φst1 (~1012 pfu/ml) in chicks challenged with ~1010 cfu/ml of S. Typhimurium, Φst1 was found to reduce the S. Typhimurium count by 5.5 log cf u/ml within 6 h of post-challenge. Systemic infection was also reduced in this group of chickens. Unlike the untreated chickens, S. Typhimurium was not detected in the liver, heart and spleen of chicks throughout the sampling period in Φst1 treated chickens. Φst1 (~1. 6 log pfu/ml) was found to persist in the caeca wall of chicks at and after 48 h post-challenge. In conclusion, Φst1 might serve as a potential therapeutic agent to control and reduce the Salmonella count in caeca content of chickens. However, further optimisation of both dosage and alternative routes of phage administration should be carried out to enhance the efficacy of the phage.